Editorial. Issue 7 (July 2019) - Mansfield-Devine, Steve
Abstract : The past few years has been a period of virtually non-stop horror stories in the press concerning data breaches. Information security is no longer a niche area occupied by a class of Cassandras whose dire warnings are airily dismissed as cyber scaremongering.